Proposed Scalable Architecture for Analyzing Big Data in Education System - Agnihotri, Nishant; Sharma, Aman Kumar (International Journal of Computer Sciences and Engineering, 2025)
Big data have emerged very fast in the last couple of years and it came up with a number of solutions to different problems varies from effective decision making, real time decision making, and effective implementation of E-Governance etc. Information and Communication technology is the major responsible for this boom in the data. It has also given birth to number of challenges like Effective data architectures, Effective analysis algorithm, Frameworks to handle this big data. As the size of data is increasing repeatedly, it gives a challenge of scaling the frameworks which could be able to handle such data. On the basis of aforesaid problems and challenges this paper has proposed a scalable architecture for the analysis of Big Data in higher Education System.